(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Obesity has become a global health concern, contributing to various chronic diseases and reducing overall quality of life. Physical activity interventions play a crucial role in managing and reducing excess body weight in obese individuals. This research paper aims to explore and analyze the effectiveness of different physical activity interventions for weight loss in obese individuals. By examining various intervention strategies, their outcomes, and potential benefits, this study aims to provide insights into the most effective approaches for promoting weight loss and improving overall health in this population.